Permissive Commercial Contracts: A Comparative Study in Imamiyyah Jurisprudence and the Legal Systems of Iran and England - Seyed Hosein Safaii; Ali Falahati Shahabodini (پژوهش تطبیقی حقوق اسلام و غرب, 2023)
Within the realm of commercial contracts, a specific group of contracts can be classified as permissive contracts. This category includes brokerages, agency contracts, employment contracts, and commercial representation. The rules and consequences associated with permissive contracts have far-reaching implications for legislative processes, court judgments, quasi-judicial bodies, and executive authorities. The authorized status of the obligated party and the presence of a trust description are two crucial factors determining the nature of these contracts. If the fulfillment of the permissive obligation lacks a trust description or occurs outside the boundaries of authentic consent, it constitutes a breach of contract or, at the very least, renders the contract non-binding. The findings of this comparative research reveal that within the legal system of England, such contracts are recognized as forms of agency contracts or representation. In Imamiyyah Jurisprudence, although no specific discussion has emerged regarding commercial permissive contracts due to their novelty, based on the general principles established in Imamiyyah Jurisprudence, these types of commercial transactions can be classified as permissive contracts. In the legal system of Iran, considering the challenges addressed in legal doctrine, there is overall compatibility between commercial permissive contracts, Imamiyyah Jurisprudence, and the legal system of England.